Improved efficiency in front-side illuminated dye sensitized solar cells based on free-standing one-dimensional TiO2 nanotube array electrodes. (15th May 2019) - Peighambardoust, Naeimeh Sadat; Asl, Shahin Khameneh; Mohammadpour, Raheleh; Asl, Shahab Khameneh
Graphical abstract: Highlights: TiO2 nanotubes were fixed on fluorine–tin-oxide glass without the TiO2 powder paste. Different doping levels of TiO2 nanotube photoanodes were studied via EIS method. Band gap narrowing was studied by comparing semiconductor and semi-metallic TiO2 . The one-diode model for equivalent circuit was used to fit the experimental I-V. The efficiency of N-doped TiO2 nanotube with both end open was enhanced about 8%. Abstract: Although morphological disorder of nanotube structure is further down than the nanoparticular electrode, its density of traps are the hindering effects in the charge transport. In this study, crack-free TiO2 nanotube membranes, which obtained through a re-anodizing process, are fixed on transparent fluorine–tin-oxide glass by applying a few drops of Titanium Isopropoxide without needing the TiO2 powder paste. Front-side illuminated dye sensitized solar cells fabricated by undoped, N-doped and blue TiO2 nanotube membranes are investigated. The electrical characteristics of TiO2 nanotube based dye sensitized solar cells are followed by theoretical analysis using simple one-diode model. Morphology improvement is utilized to remove top irregular layers and the efficiency can be increased up to 56%. Annealing temperature, dopant, and tube orientation effects are examined on the cell efficiencies. The results show that elevating annealing temperature from 480 to 520 °C improve the cell efficiency up to 70%. Also, in the N-doped TiO2 nanotube membranes, improvement in efficiency is observed up to 40% as compared to undoped samples. Finally, different orientations of N-doped TiO2 nanotubes are studied and it is found that the through-hole morphology of N-doped TiO2 nanotube membrane shows noteworthy enhancement and an efficiency of about 8%.